Halfway to hell - Johnstone, William W.; Johnstone, J. A. (A Slick Parker western, 2025)
"As the deputy sheriff in a small Missouri town, 'Slick' Parker Jones doesn't have much to do except get drunk and chase saloon girls. Life is pretty dull in Rory's Junction--until Slick sees the wanted poster for a notorious train robber. Parker's never met an actualoutlaw before. He's never faced any real dangers, to be honest. Butwhen that wanted man staggers into Parker's nightly watering hole--half dead, with a hole in his gut and a bloody map in his hand--the young deputy's life takes a wild turn--quite possibly fatal"--